2018
DOI: 10.1590/s1679-87592018149206601
|View full text |Cite
|
Sign up to set email alerts
|

Different silicon forms sinalize an input of urbanized river and indicate the presence of phytoplankton with silicon structures in the tropical coastal area of Recife (PE-Brazil)

Abstract: The urbanized areas mark its presence in the hydrological systems with some biogeochemical signs including silicon inputs. Natural influence of leaching and erosion is done by silicate contribution and sometimes, the agriculturally soil contains microphytoliths and contributes with biogenic silica. Once in the hydrological system, the silicon can integrate the biogeochemical cycles showing a balance or not between inorganic and biological forms that reveals a tendency of processes that occur in each sector of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Chlorophyll-a concentrations showed significant negative correlations with temperature and salinity, while positive correlations were observed with dissolved silicate and BSi in a study by Bastos and Braga (2018), confirming the link with siliceous organisms. Suspended particulate matter (SPM) exhibited significant correlations with silicate, BSi, and LSi, indicating their association.…”
Section: Bastos and Bragamentioning
confidence: 53%
See 1 more Smart Citation
“…Chlorophyll-a concentrations showed significant negative correlations with temperature and salinity, while positive correlations were observed with dissolved silicate and BSi in a study by Bastos and Braga (2018), confirming the link with siliceous organisms. Suspended particulate matter (SPM) exhibited significant correlations with silicate, BSi, and LSi, indicating their association.…”
Section: Bastos and Bragamentioning
confidence: 53%
“…For instance, Braga et al (2004) reported a benthic dissolved silicate anomaly (~4,000 m depth) in the Congo margin, indicating the transfer of Si from land to the ocean through the Congo River Canyon. Although studies in coastal tropical areas are scarce, Bastos and Braga (2018) observed dissolved silicate concentrations of up to 14.40 µmol L -1 , maximum LSi of 25.76 µmol L -1 , and BSi concentrations of 7.39 µmol L -1 in the coastal area of Recife, influenced by fluvial inputs from the Capibaribe and Beberibe rivers.…”
Section: Bastos and Bragamentioning
confidence: 94%